The protective effect of vagus nerve stimulation against myocardial ischemia/reperfusion injury: pooled review from preclinical studies - Xu, Yu-Peng; Lu, Xin-Yu; Song, Zheng-Qi; Lin, Hui; Chen, Yi-He (Frontiers in Pharmacology, 2023)
Myocardial ischemia-reperfusion (I/R) injury markedly undermines the protective benefits of revascularization, contributing to ventricular dysfunction and mortality. Due to complex mechanisms, no efficient ways exist to prevent cardiomyocyte reperfusion damage. Vagus nerve stimulation (VNS) appears as a potential therapeutic intervention to alleviate myocardial I/R injury. Hence, this meta-analysis intends to elucidate the potential cellular and molecular mechanisms underpinning the beneficial impact of VNS, along with its prospective clinical implications.A literature search of MEDLINE, PubMed, Embase, and Cochrane Database yielded 10 articles that satisfied the inclusion criteria. VNS was significantly correlated with a reduced infarct size following myocardial I/R injury [Weighed mean difference (WMD): -25.24, 95% confidence interval (CI): -32.24 to 18.23, P < 0.001] when compared to the control group. Despite high heterogeneity (I 2 = 95.3%, P < 0.001), sensitivity and subgroup analyses corroborated the robust efficacy of VNS in limiting infarct expansion. Moreover, meta-regression failed to identify significant influences of pre-specified covariates (i.e., stimulation type or site, VNS duration, condition, and species) on the primary estimates. Notably, VNS considerably impeded ventricular remodeling and cardiac dysfunction, as evidenced by improved left ventricular ejection fraction (LVEF) (WMD: 10.12, 95% CI: 4.28; 15.97, P = 0.001) and end-diastolic pressure (EDP) (WMD: -5.79, 95% CI: -9.84; -1.74, P = 0.005) during the reperfusion phase. Conclusion VNS offers a protective role against myocardial I/R injury and emerges as a promising therapeutic strategy for future clinical application.